Characterization of neutralizing monoclonal antibodies directed against tetanus toxin fragment C. (January 2014) - Yousefi, Mehdi; Tahmasebi, Fathollah; Younesi, Vahid; Razavi, Alireza; Khoshnoodi, Jalal; Bayat, Ali Ahmad; Abbasi, Ebrahim; Rabbani, Hodjatallah; Jeddi-Tehrani, Mahmood; Shokri, Fazel
Abstract Clostridium tetani causes a life-threatening infectious disease by production of tetanus neurotoxin (TeNT), a 150 kDa molecule composed of light (LC) and heavy chain (HC) polypeptides. The TeNT HC contains an N-terminal domain critical for LC translocation and a C-terminal toxin receptor-binding domain known as fragment C. Despite extensive investigations on epitope specificity of anti-TeNT antibodies, the immunodominant neutralizing epitopes of the toxin are poorly defined. This study describes the generation and characterization of four monoclonal antibodies (MAb) specific for TeNT. The characteristics of each MAb were explored in terms of isotype, specificity, affinity, and immuno-globulin heavy chain variable region (IGHV) gene usage using ELISA, Western blotting, and sequencing techniques. The toxin neutralizing activity of the MAbs was also investigated using the in vitro GT1b neutralizing assay. The data demonstrated that all MAbs bind to tetanus toxin and toxoid. Sub-fragments binding analysis showed that two MAbs react with fragment C, one with both fragment C and LC, and one with LC. Only the two fragment C-specific MAbs were able to neutralize the toxin. Sequencing of the expressed VH and VL genes revealed rearrangements of various VH and VL gene segments in all hybridoma clones. Clonality of the hybridomas was also confirmed by a competition assay that showed recognition of distinct epitopes by these MAbs. The results suggest the importance of TeNT fragment C in terms of immunogenicity and toxin neutralization activity.